'Me I feel proud in my uniform': the personal value of being a palliative care community volunteer. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Jack, Barbara; Kirton, Jennifer; Merriman, Anne; Birakurataki, Jerith
Abstract : Background: Approx 27 000 new cases of cancer are reported in Uganda in each year affecting 1.5% of the population. A shortage of Doctors, wide geographical distribution, and poor transport systems lead to many patients experiencing severe uncontrolled symptoms. Hospice Africa Uganda developed a community volunteer worker programme where local villagers are trained to identify patients with palliative care needs. The volunteers refer patients to the hospice and provide basic care and support for patients and families. A training course with ongoing support has resulted in 85 volunteers practicing out of the hospice in Kampala (40) and Hoima (45).The volunteers receive no payment, except for a bicycle enabling them to reach remote areas. Aim: To explore personal impact of being a palliative care community volunteer. Methodology: A qualitative methodology using semi structured individual and group tape recorded interviews was adopted for the study. Data was collected from the volunteers based in two sites (Hoima and Kampala). A purposive sample of 32 volunteers participated in the study. Data was analysed for emerging themes using thematic analysis. Results: The volunteers all reported how they found the role to be of great value to themselves, including having an increased knowledge and satisfaction at helping the dying in their villages. Interestingly they all commented on the pride of being a volunteer, how they felt when they put on their uniform and the resulting respect they received. Discussion: This paper will discuss these findings as well as the challenges that the volunteers are finding regarding language barriers and old bicycles.